Analysing the change of sagittal balance in patients with Lenke 5 idiopathic scoliosis - Ozkunt, Okan; Karademir, Gokhan; Sariyilmaz, Kerim; Gemalmaz, Halil Can; Dikici, Fatih; Domanic, Unsal (TURKISH ASSOC ORTHOPAEDICS TRAUMATOLOGY, 2017)
Objective: The aim of this study was to evaluate preoperative and postoperative spinopelvic parameters and the influence of lowest instrumented vertebrae on sagittal parameters in Lenke 5 Adolescent Idiopathic Scoliosis (AIS) patients. Methods: A total of 42 patients (37 females, 5 males

mean age: 16.71 3.46 years) were included in the study. Preoperative and postoperative last follow up lumbar lordosis (LL), thoracic kyphosis (TK), pelvic tilt (PT), pelvic incidence (PI) and sacral slope (SS) angles measured. By stopped fusion in L3, L4 or L5 we divided the group into three parts. Results: Mean follow-up was 43 months. Preoperatively, the mean TK and LL were 36.8 and 55.3. At the last follow up, the mean TK and LL were 27.1 and 49.0 degrees, respectively. Preoperatively, the mean PI, PT and SS were 53.3, 16.1 and 37.4 degrees. At the last follow up, the mean PI, PT and SS were 52.7, 19.9 and 33.0 respectively. Significant differences were observed for SS (p = 0.003), TK (p = 0.004), LL (p = 0.012) and PT (p = 0.013) postoperatively for all patients. According the L3 and L4 groups there is significant difference in SS, LL (p = 0.013) and PT (p = 0.018) which means a significant decrease occurs in SS and LL when the distal fusion level changes from L3 to L4 but significant increase in PT in L3 group to compensate spinopelvic change after surgery. Conclusion: The selection of more distal level for fusion adversely affects the compensation mechanisms of sagittal balance in Lenke 5 AIS patients. Level of Evidence: Level IV, Therapeutic study. (C) 2017 Turkish Association of Orthopaedics and Traumatology. Publishing services by Elsevier B.V.
Keywords: Lenke 5; Scoliosis; Sagittal; Spinopelvic; Compensate